Legal issues regarding the online music industry. - Chang, Andy. (2008)
This project aims to assess how legal issues have shaped the online music industry to date and to evaluate the knowledge that members of the public have in relation to the legal framework governing the online music industry and the specific changes they would liketo see effected to this framework.